OPTIMALISASI ZIS DAN PENGHAPUSAN PAJAK: SEBAGAI UPAYA PENINGKATAN KEMANDIRIAN EKONOMI MASYARARAT MISKIN DI ERA OTONOMI DAERAH - Sofyan Eko Putra (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
Poorness represent the important problems faced by the Indonesian nation, various effort have been conducted by government, but pursued with the fundamental constraint development failure, till factors of moral hazard make the poverty problems always become the new problems.Zakah, infaq, and shadaqah (ZIS) representing the part of fiscal instrument of Islam, needed in overcome poverty, that is passing gift program special economic incentive (zakat), and extra incentive from infaq and shadaqah as capital of the poor deceiveness through the development in pattern of partner and financing.On the other side, tax as conventional fiscal instrument, up to now still becomes the backbone ofAPBN in order to prosperity distribution.The aim of this paper is provide the fiscal analysis through the optimize of ZIS and tax abolition in context to rising the economic independence of poor society.Resolving through the optimize of ZIS and tax abolition expected applicable utilize the rising of economic independence of poor society in autonomy era.